A Novel Phospholipase D2-Grb2-WASp Heterotrimer Regulates Leukocyte Phagocytosis in a Two-Step Mechanism - Kantonen, Samuel (American Society for Microbiology, 2011)

(untitled)
Phagocytosis is a primary innate response of both macrophages and neutrophils involving the formation of filamentous actin (F-actin)-rich protrusions that are extended around opsonized pathogens to form a phagocytic cup, resulting in their subsequent internalization. The molecular mechanism for this is still not completely understood. We now show for the first time that phospholipase D2 (PLD2) binds to growth factor receptor-bound protein 2 (Grb2) and to the Wiskott-Aldrich syndrome protein (WASp) to form a heterotrimer complex, PLD2-Grb2-WASp, and present the mechanism of interaction. Grb2 binds to the Y169/Y179 residues of PLD2 using its only SH2 domain, and it interacts with the poly-proline region of WASp using its two SH3 domains. The PLD2-Grb2-WASp heterotrimer can be visualized in early phagocytic cups of macrophages ingesting opsonized red blood cells, where it associates with polymerized actin. Cup colocalization and phagocytosis are disrupted with mutants that alter binding at either of the two proteins or by silencing Grb2 with RNA interference (RNAi). WASp association to PLD2-K758R, a lipase-inactive mutant, still occurs, albeit at lower levels, indicating that PLD2 plays a second role in phagocytosis, which is the production of phosphatidic acid (PA) and activation of phosphatidylinositol 5-kinase (PI5K) with subsequent synthesis of phosphatidylinositol 4,5-bisphosphate (PIP(2)). The latter can be blocked with RNAi, which negates phagocytosis. Lastly, a constitutively “open” active form of WASp (WASp-L270P) brings phagocytosis to its maximum level, which can be mimicked with WASp-WT plus PLD2 or plus PA. Since neither a protein-protein disruption nor lack of PLD activity completely negates cup formation or phagocytosis, we posit a two-step mechanism: PLD2 anchors WASp at the phagocytic cup through Grb2 following protein-protein interactions and also activates it, making key lipids available locally. The heterotrimer PLD2-Grb2-WASp then enables actin nucleation at the phagocytic cup and phagocytosis, which are at the center of the innate immune system function.